Effect of local anesthetic lidocaine 2% with a combination of adrenaline 1:80000 on blood sugar levels before and after anesthesia procedures at Department of Oral and Maxillofacial Surgery, Faculty of Dentistry, Universitas Sumatera Utara - Ahyar Riza; Ismi Anugrah (Journal of Dentomaxillofacial Science, 2021)
Objective: To determine the effect of Lidocaine 2% local anesthesia with a combination of adrenaline 1:80000 on blood sugar levels before and after anesthetic procedures at Department of Oral and Maxillofacial Surgery, Faculty of Dentistry, Universitas Sumatera Utara. Material and Methods: This was an experimental study with one group pretest posttest design research design. A sample of 40 patients were given a preliminary test and a final test to find out blood sugar levels before and after being given Lidocaine 2% with adrenaline 1:80000. Results: The results of the study were analyzed using the Paired t-test. The results showed a significant difference in blood sugar levels before and after the 2% lidocaine anesthesia procedure with a combination of adrenaline 1:80.000 (p = 0.00 <0.05) Conclusion: Giving 2% lidocaine local anesthesia with a combination of adrenaline 1:80.000 increased blood sugar levels in subjects and increased blood sugar levels were higher in male subjects than female subjects.